2013
DOI: 10.1308/003588413x13643054410386
|View full text |Cite
|
Sign up to set email alerts
|

ImprovIng Trauma OperatIon Notes at an EmergIng Trauma UnIt in the RegIonal Trauma Network

Abstract: The operation note is a legal document that is the surgeon's only written record of the operation. It is the professional responsibility of the operating surgeon to ensure that the operation note is complete and accurate. A clear and complete operation note is paramount to good communication as well as safe management of the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…In this study, the majority (67%) of the operative notes were written by trainees in the initial audit. For a training institution, this is commendable and the results are similar to previous studies7. However, there is no formal training for trainees in our setting on operative note writing according to standard guidelines.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In this study, the majority (67%) of the operative notes were written by trainees in the initial audit. For a training institution, this is commendable and the results are similar to previous studies7. However, there is no formal training for trainees in our setting on operative note writing according to standard guidelines.…”
Section: Discussionsupporting
confidence: 83%
“…There were significant deficiencies in the completion of details for all the other components on assessment such as age, sex, date of operation, time of operation, name of assistant, name of scrub nurse and name of theatre anesthetist. The completion rate was low in comparison to other studies47,13,14. Clinical audits and comparative studies are governed by availability of good quality study designs and adequate detailed information.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The current epidemic of defensive practice due to fear of medicolegal repercussions has had an extensive impact on neurosurgical documentation practices, resulting in more detailed documentation of procedures (7). Despite guidelines being available for the documentation of operative notes (8), many studies have demonstrated the inadequate quality of operative notes with much salient information missing, including the nature of the surgery, indication of surgery, estimated blood loss, incidence of complications, and postoperative instructions (6,(9)(10)(11). Such non-standardised documentation can lead to greater manual review times, making the extraction of relevant information more labour-intensive.…”
Section: Introductionmentioning
confidence: 99%